2007
DOI: 10.1038/sj.npp.1301532
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Cystine–Glutamate Antiporters to the Psychotomimetic Effects of Phencyclidine

Abstract: Altered glutamate signaling contributes to a myriad of neural disorders, including schizophrenia. While synaptic levels are intensely studied, nonvesicular release mechanisms, including cystine-glutamate exchange, maintain high steady-state glutamate levels in the extrasynaptic space. The existence of extrasynaptic receptors, including metabotropic group II glutamate receptors (mGluR), pose nonvesicular release mechanisms as unrecognized targets capable of contributing to pathological glutamate signaling. We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 68 publications
(111 reference statements)
5
91
0
1
Order By: Relevance
“…This suggests the involvement of other transmitter systems in the locomotor-stimulant effect of methamphetamine. In this respect, we found that methamphetamine and MGS0028 did not affect the extracellular glutamate levels in the prefrontal cortex and nucleus accumbens, although the previous microdialysis studies showed that phencyclidine increased the extracellular glutamate levels (Baker et al 2008;Moghaddam and Adams 1998). Taken together, it is likely that the mechanism for the antipsychotic effect of mGlu2/3 receptor agonists differs between the phencyclidine-and psychostimulant-induced hyperlocomotion models.…”
Section: Discussionmentioning
confidence: 66%
“…This suggests the involvement of other transmitter systems in the locomotor-stimulant effect of methamphetamine. In this respect, we found that methamphetamine and MGS0028 did not affect the extracellular glutamate levels in the prefrontal cortex and nucleus accumbens, although the previous microdialysis studies showed that phencyclidine increased the extracellular glutamate levels (Baker et al 2008;Moghaddam and Adams 1998). Taken together, it is likely that the mechanism for the antipsychotic effect of mGlu2/3 receptor agonists differs between the phencyclidine-and psychostimulant-induced hyperlocomotion models.…”
Section: Discussionmentioning
confidence: 66%
“…We will briefly discuss some of those aspects with relevance to psychosis and the model under consideration. There are high steady-state glutamate levels in the extrasynaptic space, controlled by extrasynaptic metabotropic group II glutamate receptors (mglur2), which interact with an active exchange mechanism that shuttles cystine into and glutamate out of the glial cells that surround synapses (Baker et al, 2008). As mglur2s function as presynaptic autoreceptors (Baskys and Malenka, 1991), extrasynaptic glutamate negatively modulates the synaptic release of glutamate (Moran et al, 2005).…”
Section: Pðhjdþ ¼ Pðdjhþpðhþ Pðdþmentioning
confidence: 99%
“…In a rodent model of schizophrenia, where the NMDA antagonist phencyclidine (PCP) is administered, deficits in working memory, as evaluated using a t-maze, are linked to increased synaptic glutamate release in prefrontal cortex. Baker et al showed that these deficits can be restored by increasing the activity of system x c -and, as such, inducing a negative feedback loop via group II metabotropic glutamate receptor activation, which subsequently leads to reduced presynaptic glutamate release (7).…”
Section: System X Cmentioning
confidence: 99%